PRAWNOKARNA ODPOWIEDZIALNOŚĆ SĘDZIEGO ŹLE WYPEŁNIAJĄCEGO SWOJE OFFICIUM - Palmirski, Tomasz (Zeszyty Prawnicze, 2017)
The Criminal Liability of a Judge Wrongly Fulfilling His officium Summary Bribing judges was an indispensable element of the lawsuits, especially criminal, which is reflected both in the acts issued to prevent bribery and the literature. The oldest regulations concerning this issue are included in the Law of the XII Tables, which were handed down by Aulus Gellius. It is evident from this Law that index or arbiter who adjudged in favour of the person from whom he received money, was sentenced to death. The issue of corruption appears also in the sources of the late republic. It is evident that the attempts to fight against the judges’ corruption were made in a series of acts, among others, in lex Sempronia ne quis iudicio circumveniretur. This act concerned only those who had the senatorial status and who sentenced the accused not because he was guilty but because they were bribed. In the period of the early principate and probably until the end of the classical law era, the liability of the judge was regulated above all by two acts: lex Cornelia de sicariis and lex Iulia de repetundis. However, on the basis of the passages referring to the scope of applying lex Cornelia in the principate period it appears that it is impossible to point the particular stages of the development of a corruptible judge’s liability. It can be only supposed that the original scope of the act’s applicability to the cases threatened with a death sentence in which the acquittal of the accused was adjudged, was later broadened to other crimes. Whereas, on the basis of legis Iuliae the one who, after taking a bribe, sentenced, acquitted or gave yet another verdict in compliance with the briber’s wish, was liable to a penalty. It should be stressed that this law referred not only to judges in criminal cases but also in civil ones (iudexzs well as arbiter). According to Paulus who comments on the act, lex Cornelia de sicariis provided deportation to an isle and confiscation of the property, whereas the penalty provided for in lex Iulia de pecuniis repetundis, as reported by Macer, was an exile. In case of more serious crimes such as accepting property benefit and passing a death sentence to an innocent person, the penalty was death or deportation to an isle. Iudices pedanei provided for dismissal from the curia to which the judge belonged to or an exile. In the period of principate lex Cornelia testamentaria nummaria (de falsis) dated 81 BC, issued by Sulla, was applied to the liability of a judge. This act originally referred to cases of forging wills and coins and later also to cases of giving and receiving property benefits to present false evidence and bribe a judge. Lex Cornelia testamentaria provided for a death sentence in case of sentencing humiliores. Honestiores were treated in a more mild way since they were sentenced to the confiscation of property and exile with deprivation of citizenship.